Perception of the peruvian student, is the virtual reality alternative of sustainability of the tourist destinations? - Quezada Castro, María del Pilar (2020)
The business sector linked to tourism could be affected as a consequence of the pandemic - Coronavirus, for this, it was considered necessary to know the perception of the university student, who was asked about the incorporation of virtual reality in the development of traditional tourism. The methodology includes the positivist paradigm, quantitative approach, analytical method, non-experimental design, descriptive level and transectional type. A questionnaire was applied to 147 university students from the Piura Region - Peru, belonging to the Faculties of Administration and Tourism. The results obtained allow us to conceive that the perception of the Peruvian university student is positive in relation to the implementation of virtual reality as a complementary service in the tourism sector, the need to know Information and Communication Technologies - ICT, the sustainability of tourist destinations and respect for the environment.